A new genus and species of phytoseiid mites (Acari: Mesostigmata) from southern Tunisia, with discussion of its phylogenetic position - Kreiter, Serge; Tixier, Marie-Stéphane (Zootaxa, 2006)
The phytoseiid mite Africoseiulella flechtmanni gen. nov., sp. nov. is described from specimens collected on an unknown small weed growing under palm trees in an oasis in southern Tunisia. This mite is unique in the following combination of characteristics: dorsal shield of both sexes and male ventri-anal shield eroded; all dorsal shield setae minute; peritreme very short; setae JV1, JV3, JV4 and ZV1 absent; hypostome elongate; chelicera with long median segment but digits short and edentate; legs short and without macrosetae. The phylogenetic relationships of this new genus with close taxa are analysed; its taxonomic position within the Typhlodrominae is uncertain.